THE ROLE OF SMALL BUSINESS IN PROVIDING EMPLOYMENT TO THE POPULATION IN UZBEKISTAN (Scientific electronic journal "Labor Economics and Human Capital", 2026)
This article examines the role of small businesses and private entrepreneurship in providing employment in the Republic of Uzbekistan. It examines the economic and institutional factors that contribute to the development of small entrepreneurship and job creation. Particular attention is paid to government support for small businesses, financial mechanisms for stimulating entrepreneurial activity, and their impact on the labor market. The study utilized methods of economic analysis, comparative analysis of statistical data, and a systems approach. The results demonstrate that small businesses are a key factor in ensuring employment and sustainable economic development in the country. It has been established that expanding access to financial resources, improving the institutional environment, and developing entrepreneurial infrastructure contribute to increased employment and improved well-being.
Keywords: small business, employment, entrepreneurship, economic development, government support, financing, labor market, Uzbekistan.